The Myxedema coma in children and adolescents: A rare endocrine emergency - Personal experience and review of literature : Myxedema coma in children and adolescents - De Sanctis, Vincenzo; Soliman , Ashraf; Daar , Shahina; Di Maio , Salvatore; Alhumaidi, Noora; Alali, Mayam; Sabt, Aml; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2021)
Abstract. Decompensated hypothyroidism, formerly known as myxedema coma, represents the most extreme clinical expression of severe primary or secondary hypothyroidism in which patients exhibit multiple organ abnormalities and progressive mental deterioration. The exact incidence of myxedema coma in adults is not known, but some authors have estimated that is approximately 0.22 per 100.0000 per year in the western world. Myxedema coma is more common in females and during winter months. The diagnosis of myxedema coma is primarily clinical with supportive evidence of the abnormal thyroid function tests. Clinical features vary depending on a several factors including the age of onset and the severity of the disease. In the majority of patients (95%), the cause of underlying hypothyroidism is autoimmunity, i.e., Hashimoto thyroiditis or congenital abnormalities. Rarely it occurs in secondary (central) hypothyroidism, due to thyrotropin deficiency related to pituitary disease, or pituitary-thyroid damage due to iron overload. Treatment consists of thyroid hormone replacement, correction of electrolyte disturbances, passive rewarming, treatment of infections, respiratory and hemodynamic support, and administration of stress-dose glucocorticoids. Prognosis seems to be better in children and adolescents compared to adults. The present review reports personal experience and the literature data on 13 patients.